Quantification of differences in germination behaviour of pelleted and coated sugar beet seeds using X-ray Computed Tomography (X-ray CT) - Blunk, Sebastian; Malik, Ali Hafeez; de Heer, Martine I.; Ekblad, Tobias; Fredlund, Kenneth; Mooney, Sacha J.; Sturrock, Craig J. (IOP Publishing, 2017)
Seed enhancement technologies i.e. priming, pelleting and coating have been extensively9 used throughout the last century to improve crop yield and to reduce losses associated with pest infestation. However, until recently, it has not been possible to non-destructively assess the effect of seed enhancement technologies belowground due to the opacity of soil. Using X- ray Computed Tomography (X-ray CT) we undertook a 4D visualisation of the germination process of four different sugar beet seed enhancement treatments (untreated / naked, coated, pelleted and pelleted + coated) in soil. The aim of this study was to improve the understanding of the germination process in the natural environment of the seed to inform future soil management and seed enhancement processes. Using X-ray CT we were able to quantify the germination and establishment process of different seed enhancement technologies in soil non-destructively for the first time. We observed a delay in seedling growth posed by the addition of a physical barrier, i.e. the seed coating. However, an enhanced radicle growth rate was observed in pelleted, as well as pelleted and coated seeds, after overcoming the physical barrier. The disadvantage posed by the addition of seed coating was overcome after four days of seedling growth. Further work should focus on refinements to the type and composition of the pelleting which we observed to have a retarded effect on seed germination.